Synthetic Derivatives of Polyethyleneimine with Enzyme-Like Catalytic Activity (Synzymes) - Klotz, Irving M. (1971)
A synthetic polymer has been prepared which contains dodecyl groups (to bind small substrate molecules) and methyleneimidazole side chains (as nucleophilic catalytic sites) linked to a polyethyleneimine framework. This macromolecule, with a high local concentration of binding and catalytic groups, catalyzes the hydrolysis of uncharged nitrophenyl esters in water at pH 7 with rates markedly greater than previously observed with any other synthetic substances under similar conditions.